2016
DOI: 10.29252/ijrm.14.8.519
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and protective effects of Royal jelly on histopathological changes in testis of diabetic rats

Abstract: Background:Diabetes is the most common endocrine disease. It has adverse effects on male reproductive function. Royal Jelly (RJ) has antioxidant and anti-diabetic effects and show protective effects against diabetes.Objective:This study was conducted to evaluate the effect of RJ on histopathological alterations of the testicular tissue in streptozotocin (STZ)-induced diabetic rats. Materials and Methods:In this experimental study, 28 adult Wistar rats were randomly divided into control (C), royal jelly (R), di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 33 publications
7
66
1
Order By: Relevance
“…This antioxidant property of D. arborea extracts could be associated with the enhancement of the fertility parameters observed in the current study. This result is in accordance with those of other authors using different plant materials (Bal et al, ; Ghanbari, Nejati, & Khazaei, ). The fertilising and antioxidant properties could be correlated with its androgenic effects.…”
Section: Discussionsupporting
confidence: 93%
“…This antioxidant property of D. arborea extracts could be associated with the enhancement of the fertility parameters observed in the current study. This result is in accordance with those of other authors using different plant materials (Bal et al, ; Ghanbari, Nejati, & Khazaei, ). The fertilising and antioxidant properties could be correlated with its androgenic effects.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, we found that RJ co‐treated animals exhibited enhanced pre‐implantation embryo development as well as improved sperm characteristics vs. HS‐only ones. Confirming our findings, earlier reports have shown that RJ has positive effects on histological alterations amelioration and antioxidant defence system reinforcement in male diabetic rat reproductive system (Ghanbari, Nejati, & Khazaei, ). It has been also found that RJ improves sperm kinematic parameters, DNA fragmentation and lipid peroxidation in streptozotocin‐induced diabetic animal models (Ghanbari et al, ) and protects against stanozolol‐induced sperm abnormality and embryo toxicity (Jalali, Najafi, Hosseinchi, et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…It includes major proteins with high contents of essential amino acids and peptides having high antioxidant and scavenging properties against free radicals [40] . Also, the antioxidant activity and biological benefits are due to polyphenols and phenols as flavonoids in major protein structures [41,42] .…”
Section: Discussionmentioning
confidence: 99%